Total earlobe reconstruction with a superiorly based preauricular flap - João Goulão; João Alves (Sociedade Brasileira de Dermatologia, 2016)
Abstract: An 86-year-old woman was referred for treatment of a lentigo maligna melanoma on the left earlobe, confirmed by cutaneous biopsy. The resulting surgical defect involved the earlobe's full thickness. The authors outline a simple method for reconstructing the entire lobe in one stage, without grafts, whilst offering a pleasant appearance. Earlobe deformity may be congenital or, more often, acquired due to trauma, burns or surgery. Ear lobules are an important reference point for facial symmetry and they serve decorative purposes like wearing earrings. Losing them represents an obvious aesthetic abnormality. Several methods developed to reconstruct this deformity have presented various advantages and disadvantages.